Analisis Dampak Cyberbullying pada Kesehatan Choi Jin-Ri (Sulli) Artis Korea dan Film Dokumenter Terakhirnya - Dwi Kurniawati; Khadijah Khadijah; Yasinta Citra Dewi Kurniasari; Doan Widhiandono (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to find out the impact of cyberbullying on the health of Korean artist Choi Jinri (Sulli). In this research method, we use a qualitative method or descriptive method using the note-taking technique, where we as researchers carry out an analysis by watching via the Netflix channel. Netflix released a documentary film in memory of the idol entitled